2020
DOI: 10.1016/j.jccase.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Unusual double-chambered right ventricle induced by ruptured sinus of Valsalva aneurysm: A case report

Abstract: A sinus of Valsalva aneurysm (SVA) is a rare cardiac condition. Among SVAs, the incidence of rupture is reported about 34-47% [1,2]. More than 97% of all ruptured aneurysms originated in either the right coronary sinus or the non-coronary sinus. Most SVA tended to rupture into the right ventricle (RV) or the right atrium. We describe a case of a double-chambered RV (DCRV) induced by a ruptured SVA with multi-factors. Case reportThe subject was a 54-year-old male who experienced easy fatigability on exertion. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…To accord with Nakashima et al study, our patients also had similar DCRV hemodynamics but in disagreement to their findings, our case had demonstrated the presence of abnormal muscular band or moderator band identified by TTE and cardiac MRI modalities. 3 Moreover, our study had elucidated the diagnosis of SVAs and DCRV morphology with non-invasive methods as in identical to Hu et al 5 The publication of case report literatures concerned with DCRV in SVAs association either in the presence or absence of VSD are summarized in the Table 1.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…To accord with Nakashima et al study, our patients also had similar DCRV hemodynamics but in disagreement to their findings, our case had demonstrated the presence of abnormal muscular band or moderator band identified by TTE and cardiac MRI modalities. 3 Moreover, our study had elucidated the diagnosis of SVAs and DCRV morphology with non-invasive methods as in identical to Hu et al 5 The publication of case report literatures concerned with DCRV in SVAs association either in the presence or absence of VSD are summarized in the Table 1.…”
Section: Discussionsupporting
confidence: 54%
“…But this is the first paper that has documented the presence of DCRV due to ruptured SVAs pathology and combined factors in the absence of VSD in the Indian national. Previously, Nakashima et al study had suggested the three possible mechanism for the development DCRV because of SVAs pathology as follows: protruding of right SVA into RV; presence of jet lesion and thickened RV in identical to our opinion in this case 3. We believe that our patients should have developed DCRV morphology even before the device closure itself because elevated RV stroke volume owing to left to right shunt might have resulted in stenosis and increased pressure gradient across RV mid portion.…”
supporting
confidence: 73%
See 1 more Smart Citation